2020
DOI: 10.3390/biom10060846
|View full text |Cite
|
Sign up to set email alerts
|

Carbamoyl-Phosphate Synthase 1 as a Novel Target of Phomoxanthone A, a Bioactive Fungal Metabolite

Abstract: Phomoxanthone A, a bioactive xanthone dimer isolated from the endophytic fungus Phomopsis sp., is a mitochondrial toxin weakening cellular respiration and electron transport chain activity by a fast breakup of the mitochondrial assembly. Here, a multi-disciplinary strategy has been developed and applied for identifying phomoxanthone A target(s) to fully address its mechanism of action, based on drug affinity response target stability and targeted limited proteolysis. Both approaches point to the identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Nowadays, it is generally accepted that poly-pharmacological drugs profile can produce additive or synergistic actions while reducing side effects and significantly contribute to the high therapeutic success and, in this scenario, the functional proteomics-based identification of drug targets covers a key role [ 12 ]. Recently, new strategies have been developed and applied for the identification of the protein partners of free bioactive small molecules, such as SPROX (Stability of Proteins from Rates of Oxidation), TPP (Thermal Proteome Profiling), CETSA (Cellular Thermal Shift Assay) and DARTS, which has been applied in this paper [ 13 , 14 ]. The DARTS strategy functions due to the ability of a small molecule to increase the stability of the interacting target(s) towards enzymatic proteolysis; this particular behavior can be revealed by Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) and the target(s) can be identified by a classical proteomics analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is generally accepted that poly-pharmacological drugs profile can produce additive or synergistic actions while reducing side effects and significantly contribute to the high therapeutic success and, in this scenario, the functional proteomics-based identification of drug targets covers a key role [ 12 ]. Recently, new strategies have been developed and applied for the identification of the protein partners of free bioactive small molecules, such as SPROX (Stability of Proteins from Rates of Oxidation), TPP (Thermal Proteome Profiling), CETSA (Cellular Thermal Shift Assay) and DARTS, which has been applied in this paper [ 13 , 14 ]. The DARTS strategy functions due to the ability of a small molecule to increase the stability of the interacting target(s) towards enzymatic proteolysis; this particular behavior can be revealed by Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) and the target(s) can be identified by a classical proteomics analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, limited proteolysis-coupled mass spectrometry (LiP-MS) measures proteolytic peptides that play as reporters to determine which protein regions are hugely affected by the NP interaction ( Morretta et al, 2017 ; Schopper et al, 2017 ; Del Gaudio et al, 2018 ; Hwang et al, 2020 ). In this work, we applied our consolidated DARTS and LIP-MS platform ( Ceccacci et al, 2020 ; Morretta et al, 2021a ) to disclose the interactome of an attractive bioactive NP such as artemetin (ART), a 5-hydroxy-3,6,7,3′,4′-pentamethoxyflavone ( Figure 1A ) found in many different medicinal plants such as Achillea millefolium L. , Artemisia absinthium , Artemisia gorgonum , Cordia verbenacea , Vitex trifolia , and Vitex negundo ( Ortet et al, 2008 ; De Souza et al, 2011 ; De Almeida et al, 2016 ; Wee et al, 2020 ; Martim et al, 2021 ; Sichaem et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phomoxanthone A (1) is a naturally occurring dimeric tetrahydroxanthone that possesses both an enticing molecular architecture and impressive biological properties (Figure 1). [1][2][3][4][5][6][7][8][9][10] For example, phomoxanthone A is known to have antibacterial, antimalarial, and anticancer activity. It has been observed that 1 is equally as effective at killing both cisplatin sensitive and cisplatin resistant cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Follow up studies by Monti identified carbamoyl-phosphate synthase 1 as a possible target of phomoxanthone A. [6] A separate study by Chen and Luo identified phomoxanthone A as a protein tyrosine phosphatase inhibitor. [7] However, the role of these two biomolecular targets in affecting mitochondrial disintegration is unclear leaving open the possibility of phomoxanthone A having more direct target(s) in the mitochondria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation